2019
DOI: 10.21608/ejhc.2019.187536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Negotiation Skills Training Program on Head Nurses' Time Management

Abstract: Negotiation is an essential skill for time management and it depends on the competence of the head nurse as a negotiator. Negotiation is an everyday experience and it plays a major role in all aspects of daily activities of the head nurses. Negotiation and time management are necessary management tools that head nurses utilized to organize the management activities reasonably, in addition to support their decision making. Aim: The current study aims to assess effect of negotiation skills training program on he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Specifically, the current study regarding overall factor ,demonstrated more-two fifths of nurse manager had moderate level of administrative factor at both hospital. This finding is consistent with, Habib, Afzal, Hussain, and Naseer, et al, (2019) (29) who found that one third of manager nurses had high level administrative factor. Also Hardiker, and Staniland,.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, the current study regarding overall factor ,demonstrated more-two fifths of nurse manager had moderate level of administrative factor at both hospital. This finding is consistent with, Habib, Afzal, Hussain, and Naseer, et al, (2019) (29) who found that one third of manager nurses had high level administrative factor. Also Hardiker, and Staniland,.…”
Section: Discussionsupporting
confidence: 91%